Impact of surface grafting density of PEG macromolecules on dually fluorescent silica nanoparticles used for the in vivo imaging of subcutaneous tumors - Adumeau, Laurent; Genevois, Coralie; Roudier, Lydia; Schatz, Christophe; Couillaud, Franck; Mornet, Stéphane (Biochimica et biophysica acta. General subjects, 2017)
In the context of systematically administered nanomedicines, the physicochemistry of NP surfaces must be controlled as a prerequisite to improve blood circulation time, and passive and active targeting. In particular, there is a real need to develop NP stealth and labelling for both in vivo and microscopic fluorescence imaging in a mice model. We have synthesized NIR/red dually fluorescent silica nanoparticles of 19nm covalently covered by a PEG layer of different grafting density in the brush conformational regime by using a reductive amination reaction. These particles were characterized by TEM, DRIFT, DLS, TGA, ζ potential measurements, UV-vis and fluorescence spectroscopy. Prostate tumors were generated in mice by subcutaneous injection of RM1-CMV-Fluc cells. Tumor growth was monitored by BLI after a D-luciferin injection. Four samples of PEGylated fluorescent NPs were individually intravenously injected into 6 mice (N=6, total 24 mice). Nanoparticle distribution was investigated using in vivo fluorescence reflectance imaging (FRI) over 48h and microscopy imaging was employed to localize the NPs within tumors in vitro. Fluorescent NP accumulation, due to the enhanced permeability and retention (EPR) effect, increases gradually as a function of increased PEG surface grafting density with a huge difference observed for the highest density grafting. For the highest grafting density, a blood circulation time of up to 24h was observed with a strong reduction in uptake by the liver. In vivo experimental results suggest that the biodistribution of NPs is very sensitive to slight variations in surface grafting density when the NPs present a high curvature radius. This study underlines the need to compensate a high curvature radius with a PEG-saturated NP surface to improve blood circulation and accumulation within tumors through the EPR effect. Dually fluorescent NPs PEGylated to saturation display physical properties useful for assessing the susceptibility of tumors to the EPR effect. Control of the physicochemical features of nanoparticle surfaces to improve blood circulation times and monitoring of the EPR effect. This article is part of a Special Issue entitled "Recent Advances in Bionanomaterials" Guest Editor: Dr. Marie-Louise Saboungi and Dr. Samuel D. Bader. •Small NPs sensitive to slight variations of PEG grafting density vs RES clearance•Control of PEG density can improve tumor accumulation through EPR effect.•Accurate control of PEGylation achieved by using anchoring reaction of high yield•Improved PEGylation of fluorescent NPs enables blood circulation times up to 24h.•Improved PEGylation of fluorescent NPs valuable to assess the EPR effect magnitude